Microwave Synthesis and Biological Activity of Hydrazone Derivatives Containing 1,2,3-Thiadiazole - Liu, Xing-Hai; Weng, Jian-Quan; Tan, Cheng-Xia (Asian Journal of Chemistry, 2011)
A new group of hydrazone derivatives containing 1,2,3-thiadiazole moiety were synthesized under microwave irradiation. The structures of the present hydrazone derivatives were characterized by 1H NMR, MS and elemental analysis. The biological activities of the presents compunds were investigated. The bioassay results indicated that some of these compounds exhibit moderate fungicidal activities, one compound showed 100 % inhibitory activity on cotyledon root of cucumber and all the compounds displayed no insecticidal activity.